Research on the Modeling and Kinematic Simulation Analysis of Parallel Indexing Cam Mechanism - Zhao Shitian; Fu Yingying; Zheng Lei; Xiao Haining; Lu Ziheng (Jixie chuandong)
Aiming at the design and verification of parallel indexing cam mechanism，a method of parallel indexing cam modeling and kinematic simulation analysis of indexing mechanism is proposed. Through the analysis of the indexing motion of parallel indexing cam mechanism，the mathematical model of the contour surface of parallel indexing cam is established by using the homogeneous coordinate transformation method，the data points of the contour surface are collected by software programming，the three-dimensional model of the mechanism is established by Creo and output to Adams after assembly，the virtual prototype of the mechanism is established and the kinematic characteristics are simulated. The characteristic curve of motion law drawn by simulation data is compared with the theoretical curve. The results show that，the angular acceleration curve fluctuates greatly，and the impact and oscillation of the mechanism are mainly located at the intersection of different roller exit and entry meshing stages and different roller working contour curves. The corresponding design improvement and processing measures are given，that is，adopting fillet transition working contour curve intersection，improving the sampling accuracy of contour curve data points，selecting appropriate motion rules and spline curve interpolation can reduce the impact and oscillation of mechanism motion.